Offshoring of software development from Japan to China / Nobuhiro Takahashi and Mita Li - Li, Mita (Universiti Teknologi MARA, Jengka, 2008)
This article discusses the recent development of offshoring in the software industry in Japan. Following interviews with several Japanese ICT companies, we reveal the present status and problems of offshoring software development, which cannot be recognized from its macro data. Japanese firms must expand offshoring because of increasing competition within Japan, although offshoring creates an outflow of technology and know-how to foreign firms. This outflow fosters prospective foreign competitors, and improves their technology, especially in China. Small and medium-sized Japanese software companies that lack advanced technology will face competition for survival against foreign firms in the near future. The income gap among Japanese software engineers will also increase.